A system behind the system: but is it Stanislavski?. Issue 2 (2nd July 2016) - Clare, Ysabel
Abstract: This paper outlines the results of a study of Stanislavski's fictional training texts, and addresses the difficulty that emerges because they were unexpectedly found to indicate a coherent system behind the System, provoking the question: but is it Stanislavski? The study focused exclusively on the narrative of exercises in An Actor's Work . Form revealed content: examination of narrative patterns facilitated the discovery of underlying conceptual constructs. The structure of the narrative appears to deliver a systematic encounter with a spatial adpositional model in which bodily experience originates the sensory, spatial and relational terms of inner experience, which are then applied back onto the body. Experience is embodied, and embodiment is experienced. During the training, and within the framework of the gradually emerging spatial adpositional model, Stanislavski teaches his students to manipulate naturally occurring experiential phenomena in specific ways for the purposes of acting. Addressing the subject of human experience alongside that of acting truthfully, Stanislavski uses the parallel to shed light on both. Training is thus a process of learning to manage and direct attention deliberately within the potentiated subjective experiential environment. Truthful acting, or living through the given circumstances, is reframed within this attentional environment as the creation of attention fields with which the actor enters into a specific spatio-temporal relationship that remains generative during performance. The system behind the System may correspond with contemporary neuroscientific developments. However, if a systematic, practical cognitive model can be derived from a problematic sample of Stanislavski's work, is it still Stanislavski?